Protective effect of Carica papaya leaves against oxidative stress in brine shrimps - James, Richard Johari; Halim, Hasseri; Nasir, Mohd Mursyidul Amin; Amiruddin, Fatimatul Huda; Nor Hazalin, Nurul Aqmar Mohamad (International Journal of Public Health Science (IJPHS), 2023)
Carica papaya, a type of tree from the Caricaceae family, is renowned for its medicinal benefits due to its diverse chemical composition. The leaves of Carica papaya, in particular, are commonly used in traditional medicine for their purported anti-dengue, anti-malarial, antioxidant, and anti-inflammatory properties. However, despite their widespread use, there is limited research available on the antioxidant characteristics of Carica papaya leaves. This study aimed to examine the potential protective effects of Carica papaya leaves methanolic (CPLM) extract against oxidative stress in Artemia salina (brine shrimp). To evaluate the antioxidant potential of CPLM extract, two commonly used antioxidant activity assays, 2,2-diphenyl-1-picrylhydrazyl (DPPH) and Ferric reducing antioxidant power (FRAP) assays, were performed. Additionally, an oxidative stress protection assay was carried out by exposing ten Artemia salina nauplii to CPLM extract for one hour before exposing them to hydrogen peroxide (H2O2). The results of this study showed that the CPLM extract has antioxidant properties. Additionally, the oxidative stress protection assay revealed that the CPLM extract increased the survival rate of Artemia salina nauplii exposed to H2O2. The study suggests that the CPLM extract obtained from Carica papaya leaves possesses antioxidant properties. It can provide protection against oxidative stress caused by hydrogen peroxide in Artemia salina.